2012
DOI: 10.1016/j.jtbi.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor growth modeling based on cell and tumor lifespans

Abstract: This paper deals with the lifespan modeling of heterogenous tumors treated by radiotherapy. A bi-scale model describing the cell and tumor lifespans by random variables is proposed. First- and second-order moments as well as the cumulative distribution functions and confidence intervals are expressed for the two lifespans with respect to the model parameters. One interesting result is that the mean value of the tumor lifespan can be approached by a logarithmic function of the initial cancer cell number. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
7
8
0
Order By: Relevance
“…Developing the probabilistic model [16], the effects of the probability that a target inactive after a dose fraction ( ), and the probability that a target reactive again after the repair mechanism ( ) have been studied numerically. Finally, we have shown that the results of our study are in good agreement with the results presented in [17].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Developing the probabilistic model [16], the effects of the probability that a target inactive after a dose fraction ( ), and the probability that a target reactive again after the repair mechanism ( ) have been studied numerically. Finally, we have shown that the results of our study are in good agreement with the results presented in [17].…”
Section: Resultssupporting
confidence: 91%
“…According to this graph the tumor lifespan for n=10 2 , 10 3 , 10 4 , 10 5 is 11, 16, 22, 27, respectively. The obtained results from this graph are in very good agreement with the results presented in [17]in Fig. 5(a).…”
Section: Numerical Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Unfortunately, the associated computational cost is heavy. Several stochastic modeling paradigms have been proposed to describe heterogeneity in tumors such as Markov chains [23,28,29,36], branching processes [25,35,10,16,37,41,13,31] and even stochastic di↵erential equations [11,7,1], but they were all focused on the steady-state responses of cell populations.…”
Section: Introductionmentioning
confidence: 99%